Human Resources and Technology Integration in Effective Public Management - Budi Gunawan; Barito Mulyo Ratmono; Denok Kurniasih; Paulus Israwan Setyoko (Indonesian Association for Public Administration, 2023)
This study aims to explore effective public management within the framework of the integration of human resources and technology. By utilizing current literature review approaches, this study focuses on sources published within the last decade. Employing keywords related to human resource and technology integration on platforms like Google Scholar, the research aims to extract relevant and significant information from a wide range of scholarly materials. The findings in this study confirm that the integration of human resources and technology in public management is an essential foundation for creating responsive, transparent , and high-quality public services. Managing public management and optimizing public services in accelerating technology includes using digital platforms; human adaptation to technology; transparency and participation of the technology community; and data security. Meanwhile, the integration of human resources and technology in innovation and development can be described in the use of technology and data analysis; collaboration, and improvement of human resources; as well as a survival strategy not to change. Finally, to see the management of change in public management in a technological framework from the aspects of technology adoption, changes in organizational culture, service efficiency and improvement, HR training and development, and monitoring and evaluation.